(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Psoriasis is a chronic autoimmune skin disease characterized by inflammation and hyperproliferation of keratinocytes. Despite its complex etiology, advances in medical research have led to various modern treatment methods, including biological therapy, systemic medications, phototherapy, and novel topical treatments. This article reviews the latest therapeutic approaches and their efficacy in managing psoriasis.